Housework Allocation in Germany: The Role of Income and Gender Identity. (28th February 2017) - Procher, Vivien; Ritter, Nolan; Vance, Colin
Abstract : Objectives: This article analyzes how couples allocate housework against the backdrop of three questions: (1) Does an individual's income—both in absolute and relative terms—influence his or her contribution to housework? (2) If so, does the magnitude of this influence differ by gender? and (3) How important are traditional gender roles on housework allocation? Methods: We apply panel regression techniques to longitudinal German household data. Results: We find that as both the share and absolute level of income increase, the amount of housework undertaken by wives and husbands decreases. Traditional gender roles also underpin housework allocation, which is evidenced by women increasing their housework if they earn more than their partner. Conclusion: While we find a negative association between earnings and housework, policy measures to ease the double burden borne by working women may have only a modest effect owing to the persistence of traditional gender conceptions.